Severity of menopausal symptoms on quality of life among working women - S Ramyashree; Jacintha Veigas; Deepa Kanagal (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Menopause is experienced by every woman; some women attain it very early as they reach 42 years old. This happens when there is a dysfunction of follicles. The symptoms experienced by the women vary from mild to severe. The study aims to identify the severity of menopausal symptoms and their effect on the quality of life (QOL) among working women. MATERIALS AND METHODS: A cross-sectional research design was used for the study. A total of 93 menopausal working women were selected by using the nonprobability sampling technique. A standardized menopausal symptom rating scale and menopausal quality of life scale were used. RESULTS: The mean age of women employees was 49.8 with a standard deviation (SD) of 8.6, and almost half the number of subjects had completed diplomas and graduated. The majority of the women (77.7%) belonged to nuclear families. More than half of the subjects (59.6%) were having above 30,000 monthly incomes. More than three-fourths of the participants were married. Nearly half the number of subjects (46.8%) had completed diplomas, and 47.9% of working women were graduates. Nearly one-quarter of the subjects had severe menopausal symptoms, The most-reported menopausal symptoms were hot flush (57%), sweating (62%), muscle and joint problems (52%), depressive mood (45%), and irritability (51%). About 22.5% of women had a low quality of life. The study realizes that there is a positive correlation (r = 0.71, P = 0.001*) between menopausal symptoms and quality of life. CONCLUSION: The study justifies that menopause causes both physical and psychological problems. The stress at the workplace causes more mental disturbance and physical fatigue in working menopausal women, directly affecting their quality of life.